1994
DOI: 10.1136/thx.49.11.1152
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nucleolar organiser regions and DNA flow cytometry in the evaluation of pleural effusion.

Abstract: AgNOR method, which is rapid and easy to perform, may be a useful adjunct to flow cytometry, S phase fraction analysis and conventional cytology in the routine diagnosis of malignant pleural effusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…Indeed, 87% of HSIL were positive for high AgNOR counts and, interestingly, 85% for high SPF, which confirms that they could be useful proliferation markers (table 2). These results are also in accordance with previous studies conducted elsewhere [29, 30], which found that AgNOR quantitation reflects changes in DNA ploidy as well as cell proliferation. Moreover, in this study, we have also found a correlation between the increase in SPF and AgNOR counts in the ASCUS and LSIL groups (table 2).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Indeed, 87% of HSIL were positive for high AgNOR counts and, interestingly, 85% for high SPF, which confirms that they could be useful proliferation markers (table 2). These results are also in accordance with previous studies conducted elsewhere [29, 30], which found that AgNOR quantitation reflects changes in DNA ploidy as well as cell proliferation. Moreover, in this study, we have also found a correlation between the increase in SPF and AgNOR counts in the ASCUS and LSIL groups (table 2).…”
Section: Discussionsupporting
confidence: 83%
“…Several studies also reported that aneuploid DI and high SPF significantly correlated with patient survival, representing a subgroup with a poor prognosis in cancer cases [30, 39, 40]. The survival of patients who had SPF >12% was significantly worse than that of those who had SPF ≤12% in cervical cancer cases [39].…”
Section: Discussionmentioning
confidence: 99%
“…Mesothelial cells infrequently have a high S-phase fraction in reactive conditions (up to 16% by image analysis), with less variance from the average (5.4%). Similar results have been reported previously (26).…”
Section: Dna and S Phasesupporting
confidence: 82%
“…FCM DNA analysis has been shown to be useful for the detection of malignant cells in a variety of serous effusions. [13][14][15]23,24,27,28,32 The criteria for the determination of aneuploidy differs from author to author. We consider as aneuploidy only those cases with a clearly separate extra peak separable from the diploid cell population.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to that reported in other effusion studies. [13][14][15]23,24,27,28,32 In all these studies, the major dilemma in applying FCM to detecting malignant cells is the premise that an absence of aneuploid cells indicates absence of malignancy. All tumors can contain diploid-only cells, 4,10 and aneuploidy is not always synonymous with malignancy.…”
Section: Discussionmentioning
confidence: 99%